Evaluation of a longitudinal Indigenous health elective in family medicine - Zaretsky, Lisa; Crooks, Rachel; Whalen-Browne, Molly; Gausvik, Amy Lorette; Roach, Pamela (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2025)
Background: In response to the Truth and Reconciliation Commission of Canada Calls to Action 22 to 24 around health, the Department of Family Medicine at the University of Calgary piloted a novel Indigenous Health Longitudinal Elective (IHLE) to give first year residents longitudinal experiences in Indigenous healthcare environments. The purpose of this evaluation was to capture the successful qualities and identify areas for improvements to ensure feasibility of the IHLE pilot program.Methods: Between November 2022 and April 2023, semi-structured interviews were completed with seven participants of the IHLE and included a mix of residents, preceptors, and clinic staff members. Qualitative thematic analysis was used to gain an in-depth understanding of the IHLE program experiences of all participants.Results: Benefits of the IHLE program include a deeper understanding of the values and priorities critical to working in healthcare with Indigenous peoples in Southern Alberta. Areas for improvement include clarity around IHLE program structure; clearly defining roles and responsibilities for preceptors; increased opportunities for reciprocity and relationality; and a deeper self-reflection process.Conclusion: Recommendations for future iterations of the IHLE include ensuring preceptors are trained and engaged, while providing residents more opportunities for relationality and peer debriefing. Results from this study may also help inform future Indigenous health programming in family medicine.